Eksplorasi Pemetaan Pelanggan dan Prioritas Pengembangan Jaringan Internet : Pendekatan Sistem Informasi Geografis Berbasis Web dan AHP - Suhartini, Suhartini; Ahmadi, Hamzan; Mandala Putra, Hadian; Haeruzzikri, Haeruzzikri; Muhammad Djamaluddin (Fakultas Teknik Universitas Hamzanwadi, 2024)
ArsyaNet, a local internet service provider, strives to deliver fast and reliable internet access to its customers. This study aims to implement a web-based Geographic Information System (GIS) for customer mapping and network development prioritization using the Analytic Hierarchy Process (AHP) method at ArsyaNet. Leaflet is employed to map the distribution of ArsyaNet customers within the RT/RW network in the Pringgasela District. The main objective of this research is to accurately and efficiently map the distribution of internet customers to support optimal network development. By integrating AHP into the GIS, customer preferences and other relevant factors such as access speed, service quality, and infrastructure needs in specific areas will be considered in determining the priority locations for network development. The AHP method allows for the grouping of customers based on their preferences and determining locations by considering weights on each relevant aspect. Integrating Leaflet into the GIS enables accurate and interactive mapping results using a lighter map compared to the Google Maps API. This research is conducted to enhance the quality of internet services provided by ArsyaNet by better understanding the needs and preferences of customers in selecting internet service providers and their customer distribution.